Novel PET Imaging of Inflammatory Targets and Cells for the Diagnosis and Monitoring of Giant Cell Arteritis and Polymyalgia Rheumatica - van der Geest, Kornelis S. M.; Sandovici, Maria; Nienhuis, Pieter H.; Slart, Riemer H. J. A.; Heeringa, Peter; Brouwer, Elisabeth; Jiemy, William F. (Frontiers in Medicine, 2022)
Giant cell arteritis (GCA) and polymyalgia rheumatica (PMR) are two interrelated inflammatory diseases affecting patients above 50 years of age. Patients with GCA suffer from granulomatous inflammation of medium- to large-sized arteries. This inflammation can lead to severe ischemic complications (e.g. irreversible vision loss and stroke) and aneurysm-related complications (such as aortic dissection). On the other hand, patients suffering from PMR present with proximal stiffness and pain due to inflammation of the shoulder and pelvic girdles. PMR is observed in 40-60% of patients with GCA, while up to 21% of patients suffering from PMR are also affected by GCA. Due to the risk of ischemic complications, GCA has to be promptly treated upon clinical suspicion. The treatment of both GCA and PMR still heavily relies on glucocorticoids (GCs), although novel targeted therapies are emerging. Imaging has a central position in the diagnosis of GCA and PMR. While [18F]fluorodeoxyglucose (FDG)-positron emission tomography (PET) has proven to be a valuable tool for diagnosis of GCA and PMR, it possesses major drawbacks such as unspecific uptake in cells with high glucose metabolism, high background activity in several non-target organs and a decrease of diagnostic accuracy already after a short course of GC treatment. In recent years, our understanding of the immunopathogenesis of GCA and, to some extent, PMR has advanced. In this review, we summarize the current knowledge on the cellular heterogeneity in the immunopathology of GCA/PMR and discuss how recent advances in specific tissue infiltrating leukocyte and stromal cell profiles may be exploited as a source of novel targets for imaging. Finally, we discuss prospective novel PET radiotracers that may be useful for the diagnosis and treatment monitoring in GCA and PMR.